Psychological pathways in enterprise participation in university-industry collaboration: how does social cognitive theory explain participation willingness? - Liu, Jun (Frontiers in Psychology, 2025)
BackgroundWith the in-depth implementation of innovation-driven development strategies, University-Industry Collaboration (UIC) has become an important pathway for promoting technological innovation and industrial upgrading. However, enterprises, as one of the main collaboration entities, show significant differences in their participation enthusiasm and depth. Existing research mainly explores UIC influencing factors from resource dependence and knowledge management perspectives, with insufficient exploration of the enterprise cognitive dimension. This study constructs an analytical framework based on social cognitive theory to systematically examine how multiple cognitive factors and environmental factors influence enterprise decision-making in UIC participation.PurposeTo reveal how observational learning, self-efficacy, outcome expectations, and policy support jointly influence enterprises’ decision-making process in UIC participation, and to explore the moderating role of organizational characteristics in this process.MethodsThrough a questionnaire survey of 300 enterprises in China’s coastal regions, this study employed Structural Equation Modeling (SEM) to analyze the influence mechanisms of observational learning, self-efficacy, outcome expectations, and policy support on enterprises’ willingness to participate in UIC.ResultsThe research found that: (1) observational learning, self-efficacy, and outcome expectations have significant positive impacts on enterprise participation willingness (β = 0.285, 0.312, 0.356, p < 0.001), with outcome expectations showing the strongest direct effect; (2) risk and cost perceptions significantly inhibit participation willingness (β = −0.245, p < 0.001), this indicates enterprises carefully weigh potential benefits against perceived risks when making UIC participation decisions; (3) policy support indirectly promotes participation willingness by enhancing enterprise self-efficacy (β = 0.298, p < 0.001); (4) enterprises’ innovation capabilities and resource endowments positively moderate the relationship between policy support and participation willingness (β = 0.187, p < 0.01).ConclusionThis research extends the application of social cognitive theory in inter-organizational collaboration research, provides empirical evidence for policy design and enterprise practice, and emphasizes the need to enhance UIC effectiveness through capacity building, differentiated policy support, and risk management.